Pengaruh Pemberian Edukasi Personal Hygiene Terhadap Gejala Scabies Pada Santri Di Pondok Pesantren Miftahul Huda Kendal - Ahmad Ghozali; Moch Aspihan; Iskim Luthfa (Journal of Health, Medical, and Psychological Studies, 2026)
Scabies is a contagious skin disease caused by infestation of the mite Sarcoptes scabiei and commonly occurs in densely populated environments such as Islamic boarding schools. Poor personal hygiene behavior is a major risk factor that facilitates the transmission of scabies. Miftahul Huda Islamic Boarding School in Kendal reported a high number of skin disease complaints over the past three months, indicating the need for health interventions in the form of personal hygiene education to prevent and reduce scabies symptoms among students. To determine the effect of personal hygiene education on scabies symptoms among students at Miftahul Huda Islamic Boarding School, Kendal. This study employed a quasi-experimental design with a one-group pre-test post-test approach. A total of 27 students were selected using simple random sampling. Data were collected using an 8-item scabies symptom questionnaire. Data analysis included descriptive analysis, Kolmogorov–Smirnov and Shapiro–Wilk normality tests, and the Wilcoxon Signed Rank Test due to non-normal data distribution. The mean scabies symptom score before the intervention was 7.85 and decreased to 0.00 after the personal hygiene education. The Wilcoxon test showed a Z value of −4.916 with a p-value of 0.000 (p < 0.05). Personal hygiene education has a significant effect on reducing scabies symptoms among students.